Pengaruh Kecerdasan Emosional dan Komitmen Organisasional terhadap Kinerja Karyawan Bagian Busana Roxy Square Mall Jember dengan Organizational Citizenship Behavior (OCB) Sebagai Variabel Intervening - Adi Putra; Dewi Prihatini; Agus Priyono (Universitas Jember, 2020)
This study aims to determine the influence of emotional intellegence and organizational commitment on the employee performance fashion department in Roxy Square Mall Jember with organizational citizenship behavior (OCB) as intervening. The population in this study were all employees working at fasion department Roxy Square Mall Jember branch as much as 210 employees and the sample used was 138 respondents. The sampling technique uses probality sampling with simple random sampling method. The research model was tested by using the path analysis. The results of this study showed that the emotional intelligence and organizational commitment had a positive effect on Organizational Citizenship Behavior (OCB). The emotional intelligence, organizational commitment and Organizational Citizenship Behavior (OCB) had a positive effect on the employee performance. Emotional intelligence and organizational commitment had an indirect effect on the employee performance through the Organizational Citizenship Behavior (OCB). When analyzed further, the percentage of direct effect was higher than the indirect effect, which showed that the mediating variable of Organizational Citizenship Behavior (OCB) had less effect on the employee performance. Keywords: Emotional Intelligence, Organizational Commitment, Organizational Citizenship Behavior (OCB), Employee Performance.